2004
DOI: 10.1002/adsc.200404037
|View full text |Cite
|
Sign up to set email alerts
|

The Use of N‐Alkyl‐2,2′‐bipyrrolidine Derivatives as Organocatalysts for the Asymmetric Michael Addition of Ketones and Aldehydes to Nitroolefins

Abstract: Abstract:The direct Michael addition of aldehydes and ketones to nitroolefins, catalyzed by N-i-Pr-2,2'-bipyrrolidine, is described. The desired 1,4-adducts are obtained in excellent yields with enantioselectivities up to 95% ee and dr up to 95 : 5 of the syn aldehyde addition product. An unexpected inversion of diastereoselectivity was observed for the addition of a-hydroxy ketones to b-arylnitroolefins with enantioselectivities up to 98% ee. The formation of an internal hydrogen bond between the OH group of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
96
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(104 citation statements)
references
References 120 publications
7
96
0
1
Order By: Relevance
“…(1) in Scheme 42]. [186] Aldol reactions between two aldehydes, a challenging process in the context of Lewis acid catalysis, has been performed …”
Section: "Organocatalysis": N-p* Lewis Base Catalysis With Aminesmentioning
confidence: 99%
“…(1) in Scheme 42]. [186] Aldol reactions between two aldehydes, a challenging process in the context of Lewis acid catalysis, has been performed …”
Section: "Organocatalysis": N-p* Lewis Base Catalysis With Aminesmentioning
confidence: 99%
“…7 Alexakis found that chiral bipyrrolidines catalyze the addition of both aldehyde and ketone to nitroolefins efficiently with high enantioselectivities and diastereoselectivities. [8][9][10][11] Kotsuki has shown that chiral pyrrolidine-pyridine conjugate bases catalyze the Michael addition of cyclohexanone with nitroolefins, giving the adducts in almost quantitative yields with excellent diastereoselectivity (up to 99:1) and high enantioselectivity (up to 99% ee). However, when isovaleraldehyde was used as the substrate, poor enatioselectivity (22% ee) was observed.…”
Section: Introductionmentioning
confidence: 98%
“…The (2S, 3S) configuration determined for product 3 is consistent with this mechanism. The inactivation of catalyst 10 is possible through the direct reaction with nitroolefin to provide E, [20] and the reverse reaction would release 10 back into the catalytic cycle. The low reactivity of aliphatic nitroolefins might be caused by low availability of free catalyst 10 through catalyst sequestration in E. In summary, we have developed the first antiselective Michael reaction of aldehydes and nitroolefins with simple primary amine/thiourea catalyst 10.…”
mentioning
confidence: 99%